Local and Systemic Antibiotic Therapy of Wounds and Burns - Pulaski, Edwin J. (1965)
Postoperative wound infection rates range between 3% for clean wounds to 28% for dirty wounds. Indiscriminate antibiotic prophylaxis is ineffective. Requisites for effectiveness are specificity of the antibiotic for wound pathogens, the achievement of therapeutic tissue levels within four to six hours of wounding, and use only for high-risk situations. Topical neomycin is recommended in special-risk clean cases. In addition, in contaminated cases, a combination of penicillin G, a biosynthetic penicillin, and broad-spectrum penicillin parenterally is used, preoperatively, intra-operatively, and immediately postoperatively. Intravenous penicillin G and a biosynthetic penicillin are used for patients with major trauma and burns.